Analysis of dynamic parameters of the KY-crystallization process - Kryvonosov, Ie.V.; Lytvynov, L.A. (Functional Materials, 2016)
The Kyropoulos method is an efficient means for the growth of large high-quality sapphire. The main drawback of this method is the absence of information about the growth rate and geometrical size of the growing crystal during the technological process. Described in the present work is a method for analyzing the dynamic characteristics of the real crystallization process. The method is based on the readings of the growing crystal weight sensor, and on a virtual image of the technological process, assumed that the crystallization interface has a conical shape characterized by a varying angle at the cone vertex.